Representasi Pandangan Dunia dan Struktur Sosial dalam Novel Fi’rān Ummī Ḥissah Karya Saud al-Sanousi: Analisis Strukturalisme Genetik Lucien Goldmann - Hayati, Husna; Rahmah, Puja; Nazaruddin, Nazaruddin; Nurlianah, Nurlianah; Warni, Ade (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This research aims to uncover the representation of the author's worldview and social structure depicted in the novel Fi'rān Ummī Ḥiṣṣah by Saud al-Sanousi through Lucien Goldmann's Genetic Structuralism approach. This research focuses on the analysis of how social structures, especially those related to sectarian tensions between Sunnis and Shiites, are reflected in the narrative and characters in the novel. Using the theory of genetic structuralism, this study examines the relationship between the social, historical, and collective consciousness conditions that shape the author's worldview and how these affect the story and character portrayal in literary works. The results of the analysis show that Saud al-Sanousi used this novel as a forum to depict social tensions that included sectarian differences in Kuwaiti society. The social structure contained in this novel shows how sectarian tensions govern the social and political life of Kuwaiti society, which affects the behavior and mindset of the characters. Thus, through an analysis of genetic structuralism, it can be concluded that the novel Fi'rān Ummī Ḥiṣṣah not only reflects the experiences of individuals in dealing with social and political conflicts, but also shows the powerful influence of social structures and collective consciousness on the author's worldview. This novel is a medium of criticism of social disintegration caused by sectarian differences, as well as depicting the search for hope in the face of future uncertainty. Genetic Structuralism, Worldview, Social Structure, Saud al-Sanousi, Fi'rān Ummī Ḥiṣṣah, Sectarian Tensions